2018
DOI: 10.1016/j.actamat.2018.06.026
|View full text |Cite|
|
Sign up to set email alerts
|

Synchrotron tomographic quantification of the influence of Zn concentration on dendritic growth in Mg-Zn alloys

Abstract: Dendritic microstructural evolution during the solidification of Mg-Zn alloys was investigated as a function of Zn concentration using in situ synchrotron X-ray tomography. We reveal that increasing Zn content from 25 wt.% to 50 wt.% causes a Dendrite Orientation Transition (DOT) from a six-fold snowflake structure to a hyper-branched morphology and then back to a six-fold structure. This transition was attributed to changes in the anisotropy of the solid-liquid interfacial energy caused by the increase in Zn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…For Mg–6Al–3Sn–0.25Mn– x Zn alloys, the volume fraction of the phases is 9.6%, 11.9%, 17.7%, 22.6%, and 24.5%, respectively. It can be considered that the formed second phase effectively reduces dendrite spacing and promotes cast grain refinement [17].…”
Section: Resultsmentioning
confidence: 99%
“…For Mg–6Al–3Sn–0.25Mn– x Zn alloys, the volume fraction of the phases is 9.6%, 11.9%, 17.7%, 22.6%, and 24.5%, respectively. It can be considered that the formed second phase effectively reduces dendrite spacing and promotes cast grain refinement [17].…”
Section: Resultsmentioning
confidence: 99%
“…They reveal that increasing Zn content from 25 wt.% to 50 wt.% causes a Dendrite Orientation Transition (DOT) from a six-fold snow-flake structure to a hyper-branched morphology and then back to a six-fold structure. This transition was attributed to changes in the anisotropy of the solid-liquid interfacial energy caused by the increase in Zn concentration [36,37]. Further, doublon, triplon and quadruplon tip splitting mechanisms were shown to be active in the Mg-38 wt.% Zn alloy, creating a hyper-branched structure.…”
Section: Microstructure Phase and Compositionmentioning
confidence: 96%
“…Therefore, this proves that as the Zn content increases, the grain size has been significantly refined. Recent papers [36,37] demonstrated that dendritic microstructural evolution during the solidification of Mg-Zn alloys was investigated as a function of Zn concentration using in situ synchrotron X-ray tomography (Shanghai Synchrotron Radiation Facility, Shanghai, China). They reveal that increasing Zn content from 25 wt.% to 50 wt.% causes a Dendrite Orientation Transition (DOT) from a six-fold snow-flake structure to a hyper-branched morphology and then back to a six-fold structure.…”
Section: Microstructure Phase and Compositionmentioning
confidence: 99%
“…There has been much attention given to magnesium alloys containing high concentrations of Zn (usually between 3 and 6 wt%) [10][11][12] and low concentrations of Ca (usually between 0.2 and 1 wt%) [13][14][15][16][17][18]. Du et al [10] found that the tensile strength of an as-extruded Mg-6 wt% Zn alloy could be effectively improved by Ca (0.36-0.82 wt%) addition.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [11] reported that during indirect extrusion process, fine-grained structures were preferentially formed in the untwinned matrix and near the intermetallic compounds in Mg-5.99Zn-1.76Ca-0.35Mn (wt%) alloy. Shuai et al [12] investigated the anisotropy of the solid-liquid interfacial energy for Mg-Zn alloys, which increased with increasing the Zn concentration to 50 wt%. Oh-ishi et al [13] obtained the highest peak hardness of a Mg-0.3Ca-Zn alloy as Zn additions up to 0.6 (at%).…”
Section: Introductionmentioning
confidence: 99%